2005
DOI: 10.1182/blood-2004-05-1722
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-binding residues lie in central regions of Duffy-binding–like domains involved in red cell invasion and cytoadherence by malaria parasites

Abstract: Erythrocyte invasion by malaria parasites and cytoadherence of Plasmodium falciparum-infected erythrocytes to host capillaries are 2 key pathogenic mechanisms in malaria. The receptor-binding domains of erythrocyte-binding proteins (EBPs) such as Plasmodium falciparum EBA-175, which mediate invasion, and P falciparum erythrocyte membrane protein 1 (PfEMP-1) family members, which are encoded by var genes and mediate cytoadherence, have been mapped to conserved cysteine-rich domains referred to as Duffy-binding-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
5
34
0
Order By: Relevance
“…Recent studies have shown that the receptor-binding residues of DBL1␣ lie in the central parts of the domain (9). Parallel experiments with other DBL orthologs have also identified receptor affinity in this region (28,29), indicating the importance of this domain in binding to host receptors.…”
Section: D Model Constructionmentioning
confidence: 76%
See 2 more Smart Citations
“…Recent studies have shown that the receptor-binding residues of DBL1␣ lie in the central parts of the domain (9). Parallel experiments with other DBL orthologs have also identified receptor affinity in this region (28,29), indicating the importance of this domain in binding to host receptors.…”
Section: D Model Constructionmentioning
confidence: 76%
“…These ␣-helical regions probably have morphological constraints but are likely to be exposed to the immune system and possibly available to function as adhesins. Furthermore, the location of the degenerate motifs in DBL1␣ correspond to the regions of fold-conservation and receptor-interaction in the DBL domains of EBA-175 and Pk␣-DBL, suggesting that PfEMP1-DBL1␣ has retained a similar conserved structure and area for receptor binding (9). However, it has to be stressed that, although DBL1␣ is a hypervariable protein domain, it contains regions with high conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding site of the R29 var1-encoded DBL␣ domain has been mapped to the central region including amino acids 133 to 366 (Cys residues 5 to 12) (20). A DNA fragment (nucleotides 399 to 1098) encoding R29 DBL␣ (20,31) fused to a hexahistidine tag at the C-terminal end was amplified by a PCR using primers 5Ј-GCA TGC CAT GGA TAG AAA TTT AGA ATA TTT GAT C-3Ј and 5Ј-CGA GTG TCG ACT CAG TGA TGG TGA TGG TGA TGA CGT GGA CAA TTT AAA TCT ATA AAG-3Ј, with a plasmid containing a DNA fragment encoding DBL␣ of P. falciparum R29 as the template.…”
Section: Expression Of Rdbl␣mentioning
confidence: 99%
“…The DBL␣ domain encoded by R29 var1, the var gene expressed by the rosetting parasite R29, binds complement receptor 1 (CR1) on erythrocytes to mediate the formation of rosettes (31). The CR1 binding residues map to the 233-aminoacid central stretch of the DBL␣ domain (20).…”
mentioning
confidence: 99%